Creative milieus as factors of regional development - Rösch, Andreas (Raumforschung und Raumordnung | Spatial Research and Planning, 2000)
This article deals with the question of what can be learnt for future regional development from the discussion on what are referred to as “creative milieus”, and with how these lessons can assist with the framing of integrated approaches to regional policy (“milieu-orientated regional policy”). But are there not also (regional) milieus which — far from being creative or innovative — are hostile to innovation, or even “sclerotic”? The author shows that it is possible to proceed from the assumption of a life-cycle for regional milieus within a heuristic model and that specific factors have to be developed in order for a milieu to be capable of being deemed “creative”. The article concludes with a number of propositions and reflections on how creative milieus can be promoted and on their relevance for regional policy.